Dynamic properties of CO2-cured foam concrete at different loading rates: Effect of the foam admixtures and addition of polypropylene fiber - Liu, Yunlin; Huo, Shangwei; Fu, Jiali; Shi, Tingbo; Guo, Dong (Frontiers in Materials, 2024)
This paper investigated the dynamic mechanical properties of CO 2 -cured foam concrete under varying conditions, focusing on the effects of foam admixture and fiber reinforcement. The study tends to enrich the knowledge regarding the performance of CO 2 -cured foam concrete under different loading rates, especially in relation to density and matrix strength. The foam admixture of the specimens ranges from 26% to 55%, achieving density from 600 kg/m 3 to 1000 kg/m 3 . The specimens were loaded at strain rates from 80 s -1 to 398 s -1 . Experimental results revealed the dynamic elastic modulus, dynamic compressive strength, and Dynamic Increase Factor (DIF) showed a strong correlation with the foam admixture and density. In addition, the addition of polypropylene (PP) fibers improved compressive properties and toughness, increasing static compressive strength by 15%. This comprehensive analysis highlights the critical role of foam admixture and fiber reinforcement in determining the dynamic properties of CO 2 -cured foam concrete and provides valuable insights for optimizing the dynamic performance of foam concrete in various construction applications.